Interleukin-2 transcription is regulated in vivo at the level of coordinated binding of both constitutive and regulated factors. - Garrity, P A (1994)
Interleukin-2 (IL-2) transcription is developmentally restricted to T cells and physiologically dependent on specific stimuli such as antigen recognition. Prior studies have shown that this stringent two-tiered regulation is mediated through a transcriptional promoter/enhancer DNA segment which is composed of diverse recognition elements. Factors binding to some of these elements are present constitutively in many cell types, while others are signal dependent, T cell specific, or both. This raises several questions about the molecular mechanism by which IL-2 expression is regulated. Is the developmental commitment of T cells reflected molecularly by stable interaction between available factors and the IL-2 enhancer prior to signal-dependent induction? At which level, factor binding to DNA or factor activity once bound, are individual regulatory elements within the native enhancer regulated? By what mechanism is developmental and physiological specificity enforced, given the participation of many relatively nonspecific elements? To answer these questions, we have used in vivo footprinting to determine and compare patterns of protein-DNA interactions at the native IL-2 locus in cell environments, including EL4 T-lymphoma cells and 32D clone 5 premast cells, which express differing subsets of IL-2 DNA-binding factors. We also used the immunosuppressant cyclosporin A as a pharmacological agent to further dissect the roles played by cyclosporin A-sensitive factors in the assembly and maintenance of protein-DNA complexes. Occupancy of all site types was observed exclusively in T cells and then only upon excitation of signal transduction pathways. This was true even though partially overlapping subsets of IL-2-binding activities were shown to be present in 32D clone 5 premast cells. This observation was especially striking in 32D cells because, upon signal stimulation, they mobilized a substantial set of IL-2 DNA-binding activities, as measured by in vitro assays using nuclear extracts. We conclude that binding activities of all classes fail to stably occupy their cognate sites in IL-2, except following activation of T cells, and that specificity of IL-2 transcription is enforced at the level of chromosomal occupancy, which appears to be an all-or-nothing phenomenon.